Análisis de liquidez de la empresa AGROBANANO - Benavides Amador, Mariela Estefania (2018)
The treatment of this case study, is directed to perform a "Analysis of liquidity of AGROBABANO" is made with the aim of generating a respective analysis to the financial statements of the same for the years 2016 and 2017. Company dedicated to the sale to the wholesale and retail of agricultural supplies, wholesale and retail of plastic materials and activities related to accounting, located in the town of Puebloviejo, Aurora Estrada Avenue and the road to Vinces. The objective of this research work is to evaluate, analyze and interpret the financial approach presented by AGROBABANO, within the aforementioned periods, since it is very important to know what is the growth that has occurred or decreased, (liquidity, obligations , etc.). In the treatment of this case, the respective ratios that will be used to carry out the analysis are justified and they are; liquidity ratio, such as current ratio, acid test ratio and working capital ratio, activity ratio such as inventory turnover, average collection period, average payment period, total asset turnover, debt ratio and profitability ratio, such as net profit margin, return on assets and return on equity. To complement this case study, horizontal analysis is carried out. For the development of this case, the method to be used was a field investigation through interviews, observations and also by conversations with the administrator in order to obtain information on the subject to be developed, and to conclude with this information bibliographic sources that is; finance and books magazines.